PERTANGGUNGJAWABAN PIDANA TENAGA MEDIS PELAKU MALPRAKTIK MEDIS GUNA MEWUJUDKAN KEADILAN - Yoelita Yoelita; Tofik Yanuar Chandra; Maryano Maryano (SINERGI : Jurnal Riset Ilmiah, 2026)
Alleged malpractice cases are currently under significant scrutiny due to the biased or unclear legal regulations governing them. This is because the legal regulations governing the qualifications for malpractice are not clearly stated. This malpractice cannot be viewed from a single scientific perspective, but also from a legal perspective. The research questions addressed in this study are the forms of medical malpractice crimes and how to apply criminal liability to medical personnel who commit malpractice to achieve justice. In this study, the author uses the theory of justice and the theory of responsibility as analytical tools. The research method in this thesis is normative juridical legal research using a statute approach, case approach, conceptual approach, and analytical approach sourced from primary legal materials consisting of the 1945 Constitution of the Republic of Indonesia, the Criminal Code, the Criminal Procedure Code, Law Number 29 of 2004 concerning Medical Practice, the Indonesian Code of Medical Ethics and existing case studies, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The results of this study conclude that the forms of medical malpractice crimes are basically acts of medical personnel committed with errors in the form of intent or negligence that are contrary to professional standards, service standards, operational procedure standards, and legal obligations and medical personnel can only be punished if proven to have committed errors in the form of intent or negligence that cause harm to patients and there is no justification or excuse. However, in law enforcement practices, the application of criminal liability to medical personnel still tends to prioritize the protection of the medical profession over the protection of patients as victims. The suggestion in this study is that the government and lawmakers need to make more specific and comprehensive regulations regarding the crime of medical malpractice in legislation, especially by providing clear boundaries regarding the differences between medical risks, medical negligence, and medical malpractice and law enforcement officials, especially investigators, prosecutors, and judges, need to apply a more substantive justice-oriented approach in handling medical malpractice cases